Translation and validation of the Malay version of the WHO-5 well-being index: reliability and validity evidence from a sample of type 2 diabetes mellitus patients - Suhaimi, Aida Farhana; Mohamed Makki, Shahidah; Tan, Kit Aun; Adzlin Silim, Umi; Ibrahim, Normala (MDPI, 2022)
The translation and validation process of the WHO-5 Well-Being Index (WHO-5) into Malay is still not yet available. This study is the first psychometric evaluation of the Malay version of the WHO-5 in a sample of 127 primary care patients with type 2 diabetes mellitus. We evaluated the internal consistency and 5-week test–retest reliability of the WHO-5 Malay, and three aspects of its validity—first, the factorial validity in relation to the factor structure of the WHO-5 Malay; second, the concurrent validity in relation to depression and diabetes-related distress; and third, the convergent validity in relation to diabetes management self-efficacy and diabetes self-care behaviors. This study had two phases. Phase 1 involved the translation of the WHO-5 into Malay language following established procedures, whereas Phase 2 involved the validation of the WHO-5 Malay. Excellent internal consistency and 5-week test–retest reliability estimates were obtained. The factorial validity of the WHO-5 was found to be unidimensional. As for concurrent validity, the WHO-5 Malay was found to be negatively correlated with depression and diabetes-related distress. The WHO-5 was found to be correlated with diabetes management self-efficacy and diabetes self-care behaviors, thereby establishing convergent validity. The WHO-5 Malay has reliable and valid psychometric properties and represents a promising tool that informs healthcare providers in making effective and holistic diabetes management.